Frontline Science: Aggregated neutrophil extracellular traps prevent inflammation on the neutrophil‐rich ocular surface. Issue 6 (12th April 2019) - Mahajan, Aparna; Grüneboom, Anika; Petru, Lenka; Podolska, Malgorzata J.; Kling, Lasse; Maueröder, Christian; Dahms, Florian; Christiansen, Silke; Günter, Lochnit; Krenn, Veit; Jünemann, Anselm; Bock, Felix; et al.
Abstract: Eye rheum is a physiological discharge, which accumulates at the medial angle of the healthy eye soon after opening in the morning. Microscopic evaluation of eye rheum revealed the presence of viable neutrophils, bacteria, epithelial cells, and particles, aggregated by neutrophil extracellular traps. We observed that in the evening, during eye closure, high C5a recruited neutrophils to the tear film and activated them. In this hypoxic area rich in CO2, neutrophils fight microbial aggressors by degranulation. Immediately after eye opening, the microenvironment of the ocular surface changes, the milieu gets normoxic, and loss of CO2 induces subtle alkalinization of tear film. These conditions favored the formation of neutrophil extracellular traps (NETs) that initially covers the ocular surface and tend to aggregate by eyelid blinking. These aggregated neutrophil extracellular traps (aggNETs) are known as eye rheum and contain several viable neutrophils, epithelial cells, dust particles, and crystals packed together by NETs. Similar to aggNETs induced by monosodium urate crystals, the eye rheum shows a robust proteolytic activity that degraded inflammatory mediators before clinically overt inflammation occur. Finally, the eye rheum passively floats with the tear flow to the medial angle of the eye for disposal. We conclude that the aggNETs‐based eye rheum promotes cleaning of the ocular surface and ameliorates the inflammation on the neutrophil‐rich ocular surfaces. Abstract : Neutrophils and aggNETs actively protect the ocular surface during diurnal tear film cycle.